GILBERTO CRESPO Y MARTINEZ AND HIS PARTICIPATION IN THE POLICY OF FOMENT DURING THE PORFIRIO DIAZ REGIME. REFLECTIONS ABOUT HIS WORK DEDICATED TO BELGIUM (Tzintzun, Revista de Estudios Históricos, 2016)
In January 1892, Gilberto Crespo y Martínez published a book entitled Belgium:commercial museums, consular service, education and industrial and commercialpropaganda. Why prepare a publication on a small European kingdom, where thewidespread practice was to study English empires and Austro-Hungarian or theFrench and American fast-growing states? The aim of this paper is to locate thereason for the approach to the Belgian model as an option within the economic andtrade policy during the Porfirio Díaz regime. A further aspect was to evaluate whatwas the impact of his experience on himself and in his long career as a diplomat.
Keywords: Diplomacy; Belgium; Economy during the Porfirio Díaz regime; Paris Exposition; Commercial Museum of Brussels